Assessment of thermal behavior of a cooling system to reduce thermal fatigue cracks in aluminum injection molds - Camargo, Sergio Antonio; Romeiro, Lauro Correa; Moraes, Carlos Alberto Mendes (Revista Liberato, 2020)
The present article aimed to test changes in cooling water temperatures of males, present in aluminum injection molds, to reduce failures due to thermal fatigue. In order to carry out this work, cooling systems were studied, including their geometries, thermal gradients and the expected theoretical durability in relation to fatigue failure. The cooling system tests were developed with the aid of simulations in the ANSYS software and with fatigue calculations, using the method of Goodman. The study of the cooling system included its geometries, flow and temperature of this fluid. The results pointed to a significant increase in fatigue life of the mold component for the thermal conditions that were proposed, with a significant increase in the number of cycles, to happen failures due to thermal fatigue.